The Integration of Semantic Mapping Strategy with Group Investigation Method to Improve Students’ Vocabulary Achievement - Anisa Al Khoiriyah; Ari Nurweni; Cucu Sutarsyah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
The aim of this research is to investigate the effectiveness of combining the Semantic Mapping Strategy with the Group Investigation Method to improve students' vocabulary achievement. While Semantic Mapping is a recognized cognitive tool, its conventional application often founders due to a reliance on individual work, which limits the exchange of linguistic ideas and prevents students from engaging in the social negotiation of meaning. To address this, the study integrates the Group Investigation Method to foster a more dynamic and collaborative learning environment. A quantitative experimental design using a pretest–posttest control group was conducted with 70 first-grade students at SMAN 2 Gading Rejo during the 2025/2026 academic year. Vocabulary achievement was measured via a multiple-choice test and analyzed using an independent samples t-test. The results revealed that the experimental group demonstrated a superior improvement in vocabulary scores, increasing from 52.69 to 82.69, compared to the control group’s increase from 52.63 to 69.89, with a statistically significant difference identified (ρ=0.000 < 0.05). This study concludes that transitioning from individual semantic mapping to group-based investigations significantly boosts vocabulary gains. However, teachers must exercise careful time management to complete all investigation phases. Future research should investigate the application of this combined strategy to other language skills, specifically writing, speaking, and listening, to determine its broader pedagogical utility.